Magnetic field effects on the conductivity of organic bipolar and unipolar devices at room temperature - Gomez, J. A.; Nueesch, F.; Zuppiroli, L.; Graeff, Carlos Frederico de Oliveira [UNESP] (Elsevier B.V. Sa, 2010)
Magnetic field effects on the conductivity of different types of organic devices: undoped and dye doped aluminium (III) 8-hydroxyquinoline (Alq(3))-based organic light emitting diodes (OLEDs), electron-only Alq(3)-based diodes, and a hole-only N,N'-diphenyl-N,N'-bis(1-naphthyl)1,1'-biphenyl-4,4'-diamine (alpha-NPD)-based diode were studied at room temperature. Only negative magnetoresistance (MR) was observed for the Alq(3)-based devices. The addition of a rubrene dye in Alq(3)-based OLEDs quenches the MR by a factor of 5. The alpha-NPD hole-only device showed only positive MR. Our results are discussed with respect to the actual models for MR in organic semiconductors. Our results are in good agreement with the bipolaron model. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Organic semiconductors; OLEDs; Magnetoresistance; Bipolaron model